Bioactive procyanidins from dietary sources: The relationship between bioactivity and polymerization degree. (May 2021) - Yang, Haixia; Tuo, Xingxia; Wang, Lingbo; Tundis, Rosa; Portillo, Maria P.; Simal-Gandara, Jesus; Yu, Yan; Zou, Liang; Xiao, Jianbo; Deng, Jianjun
Abstract: Background: Procyanidins, commonly found in plant natural sources, are polymerized forms of flavanols, which are a subclass of flavonoids. They have been reported to exhibit broad benefits to human health and used in the prevention of cancers, cardiovascular diseases, diabetes, etc. Bioactivities of procyanidins depend on many factors including the structures of procyanidins. Differences in composition of the monomers and degree of polymerization (DP) contribute to the variation in procyanidins. Scope and approach: The basic structures and natural sources of procyanidins have been summarized in detail. Importantly, the structure-activity relationships of procyanidins, especially the relationship between degrees of polymerization and their antioxidant, anticancer, antidiabetic, anti-obesity, and cardioprotective effects as well as their potential mechanisms have been reviewed in detail. Additionally, current challenges in the studies of procyanidins have been discussed. Key findings and conclusions: Procyanidins are structurally diverse compounds and can be classified as monomeric, oligomeric, or polymeric variants depending on the DP, which plays a role in manifesting various effects that are associated with human health. The diversity and complexity of these chemical compounds and the difficulties encountered in the isolation of plant procyanidins continue to be major challenges. A better understanding of this information may promote the use of procyanidins in improving human health. Highlights: Procyanidins found in foods show broad bioactive benefits for human health. Bioactivities and degrees of polymerization of procyanidins are inter-related. The mechanisms of action of procyanidins in preventing diseases are reviewed. The current challenges in procyanidins research are discussed.